Batas Otonomi Maslahah Mursalah: Kritik Terhadap Ekspansi Qiyas Masalahi di Era Post-Truth - Hendri; Haidar Ali; Zaenal Abidin; Abd. Rauf Muhammad Amin (Kartika: Jurnal Studi Keislaman, 2026)
This study examines the limits of autonomy of maslahah mursalah in Usuliyyah fiqh methodology and analyzes the critique against the expansion of qiyas problemsi (maslahah-based analogical reasoning) that blurs the distinction between naṣṣ (revealed text) and raʾy (human opinion). In the post-truth era, where facts and opinions overlap and objective truth is distorted by emotions, the validity of applying qiyas problemsi based on maslahah mursalah is reduced because the identified maslahah risks becoming zhann (speculation) rather than yaqīn (certainty). The research uses library research method with a descriptive-analytic qualitative approach. The results show that the expansion of qiyas problemsi causes epistemological weaknesses due to the inability to establish 'illat that is mundabitah (precise and stable), thereby blurring the boundaries between divine authority and human interpretation. To maintain the authority of Islamic law in the post-truth era, there is a need for reconstruction of fiqh principles that integrate the principle of al-yaqīn lā yazūlu bi al-syak, maqāṣid al-sharī'ah with digital ethics, and epistemological verification standards through tabayyun to guard against cognitive biases